2003
DOI: 10.1182/blood-2002-11-3589
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective treatment of acquired immunodeficiency syndrome–related lymphoma with dose-adjusted EPOCH: impact of antiretroviral therapy suspension and tumor biology

Abstract: The outcome of acquired immunodeficiency syndrome-related lymphomas (ARLs) has improved since the era of highly active antiretroviral therapy, but median survival remains low. We studied dose-adjusted EPOCH (etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin) with suspension of antiretroviral therapy in 39 newly diagnosed ARLs and examined protein expression profiles associated with drug resistance and histogenesis, patient immunity, and HIV dynamics and mutations. The expression profiles fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
256
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(275 citation statements)
references
References 39 publications
14
256
3
2
Order By: Relevance
“…13,14 Dynamic dose adjustment of the EPOCH regimen (DA-EPOCH) has resulted in dose escalations, limited hematopoietic toxicity, and no cardiac complications or treatment-related deaths, even in patients with acquired immunodeficiency syndrome (AIDS) -related lymphoma. [15][16][17][18] The addition of rituximab (monoclonal anti-CD20 antibody) to the conventional CHOP regimen (R-CHOP) has been reported to increase the likelihood of response and long-term event-free survival, with no overlapping toxicity, in elderly patients with poor-prognosis DLBCL. 19 The objective of this study was to assess efficacy and safety, with special attention to hematological and cardiac toxicity, of the combination of rituximab and dose-adjusted infusional CHOP chemotherapy (DA-POCH-R) for patients with poor-prognostic untreated DLBCL aged >70 years and over.…”
mentioning
confidence: 99%
“…13,14 Dynamic dose adjustment of the EPOCH regimen (DA-EPOCH) has resulted in dose escalations, limited hematopoietic toxicity, and no cardiac complications or treatment-related deaths, even in patients with acquired immunodeficiency syndrome (AIDS) -related lymphoma. [15][16][17][18] The addition of rituximab (monoclonal anti-CD20 antibody) to the conventional CHOP regimen (R-CHOP) has been reported to increase the likelihood of response and long-term event-free survival, with no overlapping toxicity, in elderly patients with poor-prognosis DLBCL. 19 The objective of this study was to assess efficacy and safety, with special attention to hematological and cardiac toxicity, of the combination of rituximab and dose-adjusted infusional CHOP chemotherapy (DA-POCH-R) for patients with poor-prognostic untreated DLBCL aged >70 years and over.…”
mentioning
confidence: 99%
“…24 Despite the three-fold increase in survival of patients with AIDS-related lymphomas, the prognosis still appears worse than HIV-negative patients with comparable disease. 24,26,27 It is unclear whether these differences between AIDS-related and non-AIDS diffuse large B-cell lymphomas reflect biological variations in the lymphoma itself, or in the immunodeficient host, or in both. A definitive understanding of the pathogenesis of AIDS-related diffuse large B-cell lymphomas is still lacking.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…34 Another study, which included cases of both AIDS-related diffuse large B-cell lymphoma and Burkitt lymphoma, has suggested that there may be a shift away from the more chemoresistant lymphomas of postgerminal center origin because of the better immune function conferred by highly active antiretroviral therapy. 26 In the present pilot study, we focused solely on diffuse large B-cell lymphomas. We found that AIDS-related diffuse large B-cell lymphomas occurred in younger patients and displayed immunoblastic morphology more often than non-AIDS cases.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…Moreover, comparing our schedule with that previously used with methotrexate or cytarabine in the most important published studies, a significant reduction of intrathecal injection occurred with comparable side effects. 19,21,[34][35][36][37][38]52 These data are reported in Table 3. This is an important matter both for patients and physicians.…”
mentioning
confidence: 99%